2008
DOI: 10.2109/jcersj2.116.481
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of octacalcium phosphate intercalated with dicarboxylate ions from calcium carbonate and phosphoric acid

Abstract: We have investigated the effect of the Ca/P molar ratio in the starting composition on the synthesis of octacalcium phosphate intercalated with dicarboxylate ions (OCPC), starting from calcium carbonate and phosphoric acid in the presence of a dicarboxylic acid, such as succinic acid, adipic acid, or suberic acid. For a Ca/P molar ratio in the starting composition of 1.6, which is the stoichiometric value for OCPC, the highest yield of OCPC with a high degree of crystallinity was obtained for the OCPC samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
(12 reference statements)
0
24
0
Order By: Relevance
“…21) Twenty mmol of phosphoric acid (H 3 PO 4 , 85%, Wako Pure Chemical Industries, Ltd., Japan) was added to 200 cm 3 of distilled water under stirring. The resultant homogeneous solution was kept at 60°C, and then 0.0266 mol of calcium carbonate (CaCO 3 , Wako Pure Chemical Industries, Ltd., Japan) was added to the solution under stirring.…”
Section: Methodsmentioning
confidence: 99%
“…21) Twenty mmol of phosphoric acid (H 3 PO 4 , 85%, Wako Pure Chemical Industries, Ltd., Japan) was added to 200 cm 3 of distilled water under stirring. The resultant homogeneous solution was kept at 60°C, and then 0.0266 mol of calcium carbonate (CaCO 3 , Wako Pure Chemical Industries, Ltd., Japan) was added to the solution under stirring.…”
Section: Methodsmentioning
confidence: 99%
“…In conventional wet processing, it is important to adjust the molar ratios of calcium ion, phosphate ion, and dicarboxylic acid in the reaction system to the stoichiometric composition, for formation of OCPC. 22) It is interesting that in contrast to conventional wet processing, an excess of Suc was needed for formation of Suc OCP in the gel-mediated process.…”
Section: Discussionmentioning
confidence: 99%
“…That value of the ratio corresponds to the stoichiometric composition of OCPC. 22) The pH of the monomer solution was adjusted to 7.9 with aqueous ammonia (Wako Pure Chemical Industries Ltd.) or nitric acid (Wako Pure Chemical Industries Ltd.), and finally the volume of solution was adjusted to 100 cm 3 Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…After thorough mixing, 15 mL of 1 M CaCl 2 was added immediately into the phosphate solution with stirring. The total PO 4 and Ca 2+ ion concentration in the prepared solution was 0.33 mM. This supersaturated calcium phosphate solution was stirred at 400600 Hz for 1 h at room temperature and pressure.…”
Section: Synthesis Of Dcpd By Solution Chemistry Processesmentioning
confidence: 99%
“…7)9) Previous studies have reported that the ideal OCP forms in the P1 triclinic space group with the Ca 8 (HPO 4 ) 2 (PO 4 ) 4 ·5H 2 O (Ca/PO 4 ratio 1.33, Ca:PO 4 = 8:6) chemical formula. 1),2),9),10) The OCP crystal structure consists of three sublayer structures along the a-axis, namely, a HAP-like layer structure (Apa: Ca/PO 4 ratio 2.00, Ca:PO 4 = 4:2), a transition structure (Tra: Ca/PO 4 ratio 1.33, Ca:PO 4 = 4:3), and a HPO 4 OH layered structure (Lay: Ca/ PO 4 ratio 0.00, Ca:PO 4 = 0:2).…”
Section: Introductionmentioning
confidence: 99%